Analysis of Consumer Satisfaction Levels at Sakura Fashion Store Using the SERVQUAL Method - Laramitha; Pajar Pahrudin; Bartolomius Harpad (STMIK Widya Cipta Dharma, 2026)
This research is motivated by the importance of understanding the level of customer satisfaction in the increasingly competitive retail fashion industry, particularly at Sakura Fashion Store. Customer satisfaction is a crucial factor in maintaining customer loyalty and enhancing business competitiveness. This study aims to analyze the level of customer satisfaction with service quality using the SERVQUAL method, which encompasses five dimensions: tangibles, reliability, responsiveness, assurance, and empathy. The research method used is a descriptive quantitative approach with data collection techniques through distributing questionnaires to 42 respondents who are consumers of Sakura Fashion Store. The data obtained were analyzed to determine the match between consumer expectations and perceptions of the services provided. The results showed that the overall level of customer satisfaction was in the category of quite satisfied to satisfied. The tangibles dimension received the highest score, while the reliability and responsiveness dimensions still require improvement. This study concludes that service quality has a significant influence on customer satisfaction. Therefore, Sakura Fashion Store is advised to improve service speed, product quality consistency, and employee ability to respond to consumer needs more effectively